3 Tesla 1H MR spectroscopy of hip bone marrow in a healthy population, assessment of normal fat content values and influence of age and sex. Issue 2 (15th May 2013) - Pansini, Vittorio; Monnet, Aurélien; Salleron, Julia; Hardouin, Pierre; Cortet, Bernard; Cotten, Anne
Abstract : Purpose: To evaluate in a healthy population normal spectroscopic fat content (FC) values of the hip bone marrow and to assess the influence of age and sex on bone marrow conversion. Materials and Methods: Eighty volunteers (40 men; 40 women; ages: 20–60 years; divided into four consecutive groups) underwent acetabulum, femoral head, femoral neck, greater trochanter, and diaphysis localized 1 H MR spectroscopy. FC values of each anatomical site were obtained according to the following formula: Fat content = CH2 /(CH2 + Water)*100. To assess bone marrow conversion, a spectroscopic conversion index (SCI) was calculated as FC neck/FC greater trochanter. Results: FC values showed a gradient as follows: greater trochanter > femoral head > femoral neck > diaphysis > acetabulum in every age group both in men and in women. SCI increased with age both in men and women, showing lower values in women for every age group. Conclusion: We obtained normal spectroscopic FC values from different areas of the hip, according to age and sex. These values may be used as reference values to evaluate, by the means of 1 H MR spectroscopy, pathological conditions affecting hip bone marrow.J. Magn. Reson. Imaging 2014;39:369–376 . ©2013 Wiley Periodicals, Inc .